(untitled) (Engrami, 2021)
We could define disgust as a feeling of revulsion arising as a response to an aversive stimulus, that induces motivation to withdraw from that stimulus. There are several instruments to measure disgust sensitivity and the most used one is the disgust elicitor inventory, the Disgust Sensitivity Scale. It is the aim of this study to validate the translation of the mentioned scale into Serbian language. The sample used for this study numbered 724 participants out of which 513 (70.9%) declared themselves female, and the average age of the participants was 28.3 (SD=6.9) ranging from 18 to 66 years. The sample was collected via an internet survey. The test battery additionally consisted out of the Depression, Anxiety and Stress Scale (DASS21) and the Patient Health Questionnaire 15 (PHQ15). We tested several scale structure models, including the one, three, five and six factor models proposed in various translations and iterations of the scale. None of them proved to achieve adequate model fit criteria in confirmatory factor analysis, but the 6-factor model has the best metrics. However, the subscales in this model have low internal consistency. We have detected an expected gender difference in summary scores. There are almost no significant correlations with any other measured constructs, casting further doubt on the scale. The scale has good temporal stability. We recommend using this scale with caution and using only the summative score, our research confirms the ever-growing body of work showing that elicitor-based disgust sensitivity scales are heavily influenced by the sociocultural environment and are difficult to replicate cross-culturally. A creation of a culture specific elicitor-based disgust sensitivity scale is probably the best solution for the measurement of this construct.